Competence gaps in software personnel: A multi-organizational study - Colomo-Palacios, Ricardo; Casado-Lumbreras, Cristina; Soto-Acosta, Pedro; García-Peñalvo, Francisco J.; Tovar-Caro, Edmundo (Computers in Human Behavior, 2013)
Today, the innovation and quality of the software industry’s products and services depend to a great extent on the knowledge, ability and talent applied by software engineers. At the same time, human aspects are recognized as one of the main problems associated with software development projects. More specifically, inefficiencies usually come from inadequate verification of software engineers’ competences. Another issue is the lack of an established career for software engineers, which adds difficulties to evaluate competences. With these challenges in mind, this paper presents a study conducted in the software industry to test competence gaps among software practitioners, comparing the 360-degree feedback results and self-evaluations with that of standard competence levels. The results of this research may be very valuable to organizations immersed in software development projects.